Variability across subjects in free recall versus cued recall. - Mah, Eric Y.; Lindsay, D. Stephen (Memory & Cognition, 2024)
Memory scientists usually compare mean performance on some measure(s) (accuracy, confidence, latency) as a function of experimental condition. Some researchers have made within-subject variability in task performance a focal outcome measure (e.g., Yao et al., Journal of Clinical and Experimental Neuropsychology, 38, 227–237, 2016). Here, we explored between-subject variability in accuracy as a function of experimental conditions. This work was inspired by an incidental finding in a previous study, in which we observed greater variability in accuracy of memory performance on cued recall (CR) versus free recall (FR) of English animal/object nouns (Mah et al., Frontiers in Psychology, 14, 1146200, 2023). Here we report experiments designed to assess the reliability of that pattern and to explore its causes (e.g., differential interpretation of instructions, [un]relatedness of CR word pairs, encoding time). In Experiment 1 (N = 120 undergraduates), we replicated the CR:FR variability difference with a more representative set of English nouns. In Experiments 2A (N = 117 Prolific participants) and 2B (N = 127 undergraduates), we found that the CR:FR variability difference persisted in a forced-recall procedure. In Experiment 3 (N = 260 Prolific participants), we used meaningfully related word pairs and still found greater variability in CR than in FR performance. In Experiment 4 (N = 360 Prolific participants), we equated CR and FR study phases by having all participants study pairs and, again, observed greater variability in CR than FR. The same was true in Experiment 5 (N = 120 undergraduates), in which study time was self-paced. Comparisons of variability across subjects can yield insights into the mechanisms underlying task performance.